Pengaruh Budaya Organisasi dan Komitmen Organisasi Terhadap Produktivitas Kerja Pegawai PDAM Tirta Kencana Kabupaten Jombang - Fajar Dwi Al Aziz; Mahfudiyanto Mahfudiyanto (BIMA : Journal of Business and Innovation Management, 2020)
The purpose of this research is to examine the presence or absence of influence between organizational culture and organizational commitment with the work productivity of PDAM Tirta Kencana employees in Jombang Regency. Using a quantitative research method and with a causal or causal approach. The results of the study explained that: (1) organizational culture does not have a partial effect on the work productivity of PDAM Tirta Kencana employees in Jombang Regency, (2) organizational commitment has a partial influence on the work productivity of PDAM Tirta Kencana employees in Jombang Regency, (3) there is a simultaneous influence between cultures organization and organizational commitment to the work productivity of PDAM Tirta Kencana employees in jombang Regency.